(untitled) (Law, State and Telecommunications Review, 2025)
[Purpose] The purpose of this study was to develop a scientific and methodological framework for legal regulation of the introduction of artificial intelligence systems to ensure cybersecurity in the defense sector of Ukraine. [Methodology] This paper evaluates the weaknesses in Ukraine’s present legislation related to AI in defense cybersecurity by comparing legislative frameworks throughout the world. Based on case studies and expert interviews, it also creates a risk assessment methodology and suggests legislative changes to close these gaps. [Findings] Thirty experts in national security, law, and cybersecurity participated in the expert survey. The study’s conclusions highlight serious flaws in Ukraine’s legal framework for governing AI in defense cybersecurity, most notably the lack of precise definitions for autonomous cyber defense systems and AI systems. It is difficult to adequately address the hazards connected to the integration of AI technology into vital defense infrastructure because of this lack of regulatory clarity. Key legal dangers are identified by the study, including possible human rights violations such as invasions of privacy, restrictions on the right to free speech, and the possibility of discrimination. Concerns about autonomous AI systems’ accountability for their deeds as well as regulatory non-compliance brought on by out-of-date or insufficient legislation are also brought to light. The paper also highlights moral conundrums that AI decision-making systems may present, which could have significant effects on both individual rights and national security. The report urges the creation of specialized law that includes precise definitions, certification procedures, accountability systems, and transparency for AI systems used in the defense industry to address these problems. These results demonstrate how urgently Ukraine must revise its legal system to guarantee that AI integration complies with contemporary technical advancements as well as the values of human rights and national security. [Practical implications] The results of the study have considerable potential for practical application in the development of regulations and cybersecurity strategies in Ukraine, especially in the context of hybrid threats and information warfare. [Originality] This study develops a scientific and methodological framework for the legal regulation of artificial intelligence systems to enhance cybersecurity in Ukraine’s defense sector. It identifies significant gaps in Ukrainian legislation, proposes the Legal Risk Assessment Matrix to evaluate AI-related legal risks, and offers legislative recommendations, including the creation of a dedicated law on AI regulation.